2009
DOI: 10.5194/acpd-9-22103-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of open crop residual burning on air quality over Central Eastern China during the Mount Tai Experiment 2006 (MTX2006)

Abstract: Abstract. The impact of open crop residual burning on O3, CO, Black Carbons (BC), and Organic Carbons (OC) concentrations over Central Eastern China (CEC) during the Mount Tai Experiment 2006 (MTX2006) was evaluated using the regional chemical transport model, the Models-3 Community Multiscale Air Quality Modeling System (CMAQ). To investigate these pollutants during the MTX2006 period in June, daily gridded emissions from open crop residual burning were developed based on a bottom-up methodology and using lan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…However, a sudden change in prevailing winds from South and Southwest to North was observed during 8–10 and 14–15 June 2006, while Mount Tai received air masses originated from East China during 22–25 June 2006 (Figure ). The impact of wheat harvest residue burning emissions in the NCP on Mount Tai aerosols was documented by previous studies [ Fu et al , ; Suthawaree et al , ; Yamaji et al , ]. Consequently, we differentiated the concentration data of hydroxy FAs into two categories as days with high (H‐BBEs: 6–7, 11–14, and 27 June 2006) and low biomass‐burning emissions (L‐BBEs: 15–26 and 28 June 2006).…”
Section: Resultsmentioning
confidence: 91%
“…However, a sudden change in prevailing winds from South and Southwest to North was observed during 8–10 and 14–15 June 2006, while Mount Tai received air masses originated from East China during 22–25 June 2006 (Figure ). The impact of wheat harvest residue burning emissions in the NCP on Mount Tai aerosols was documented by previous studies [ Fu et al , ; Suthawaree et al , ; Yamaji et al , ]. Consequently, we differentiated the concentration data of hydroxy FAs into two categories as days with high (H‐BBEs: 6–7, 11–14, and 27 June 2006) and low biomass‐burning emissions (L‐BBEs: 15–26 and 28 June 2006).…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, Shimada et al (2011) reported that OC/EC ratios and hot spots identified on MODIS images suggest that air pollution from biomass burning is transported to Cape Hedo from the Asian continent in June, although that transport was not clearly evident in the observed data of the present study. According to Yamaji et al (2009) and Kanaya et al (2008), the Mount Tai Experiment in 2006 indicated that agricultural waste burning had a considerable impact on summertime emissions in China, suggesting that the effect of biomass burning might be seasonal. Shimada et al, Aerosol and Air Quality Research, 15: 799-813, 2015 …”
Section: Identification Of Source Categories Of Aerosols Transported mentioning
confidence: 99%
“…More detailed information about the emission inventory can be found in Yamaji et al (2008). In this study, REAS emissions were mapped onto a 0.1 • ×0.1 • grid using the distribution of Streets' inventory (personal communication) with 0.1 • resolution.…”
Section: Regional Chemical Transport Modelmentioning
confidence: 99%